THE IMPACT OF LEARNING MOTIVATION ON ENGLISH LEARNING ACHIEVEMENT - NGUYEN THI MINH HUYEN; NGUYEN DUY THANH (Tạp chí Khoa học xã hội Thành phố Hồ Chí Minh, 2025)
English is the only language used in many fields such as science and technology, medicine, pharmacy, education, tourism, entertainment, business, and commerce. English also helps people improve work efficiency and increase promotion opportunities. Accordingly, employees in organizations always try to update their English proficiency by participating in English courses at training institutions. Learning motivation is one of the basic factors when learning English, helping learners achieve better learning achievement. This study has been used the expectancy-value theory, the self-determination theory, the learning motivation theory, the concept of learning achievement, and the related works to conduct an investigation and evaluate the impact of learning motivation on the English learning achievement of employees in organizations. Consequently, the findings provided that the factors of communication needs, career promotion needs, esteem needs and learning environment are related to the learning motivation. Besides, the learning motivation has a positive impact on the English learning achievement.